PERBEDAAN PENDAPATAN DAN TINGKAT RISIKO USAHA TANI PADI SISTEM TEBAS DAN NON TEBAS DI DESA SARIMULYO, KECAMATAN WINONG, KABUPATEN PATI - MARIA PUJIATI; TINJUNG MARY PRIHTANTI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
This aim of the research is to: (1) knowing the perception of paddy farmer to selling system of slash and trading system include the perception on economic aspect, social aspect, practical aspect, and risk aspect. (2) Knowing income difference of farmerÂ using slashing and tradig system (3) Comparing risk analysis and strategies to overcome the risk of rice farming with slashing and trading system. The research was conducted in February-March 2018. The type of this research is quantitative descriptive research. Respondents of this research are 30 farmers of slash system and 30 farmers of non tebas system. Data collection was obtained using survey method, field observation and structured interviews to farmers using questionnaires. The results of the study explain the perception of farmers in choosing rice sales system with non tebas system better than the slashing system. There is no difference in net income between the slashing and non-slash sales system. Based on production risks, price risks, and net income risks, a slashed rice sales system has a low risk of non-slash system. Strategies to address production risks include reducing input risks, risk reduction technologies, choosing low-risk activities, production diversification, input and product reserves and price risks include market pricing information, upcoming prices, direct sales, spreading sales.